Amorphous-to-crystal transition in the layer-by-layer growth of bivalve shell prisms. (1st April 2022) - Duboisset, Julien; Ferrand, Patrick; Baroni, Arthur; Grünewald, Tilman A.; Dicko, Hamadou; Grauby, Olivier; Vidal-Dupiol, Jeremie; Saulnier, Denis; Gilles, Le Moullac; Rosenthal, Martin; Burghammer, Manfred; Nouet, Julius; et al.
Abstract: Biomineralization integrates complex physical and chemical processes bio-controlled by the living organisms through ionic concentration regulation and organic molecules production. It allows tuning the structural, optical and mechanical properties of hard tissues during ambient-condition crystallisation, motivating a deeper understanding of the underlying processes. By combining state-of-the-art optical and X-ray microscopy methods, we investigated early-mineralized calcareous units from two bivalve species, Pinctada margaritifera and Pinna nobilis, revealing chemical and crystallographic structural insights. In these calcite units, we observed ring-like structural features correlated with a lack of calcite and an increase of amorphous calcium carbonate and proteins contents. The rings also correspond to a larger crystalline disorder and a larger strain level. Based on these observations, we propose a temporal biomineralization cycle, initiated by the production of an amorphous precursor layer, which further crystallizes with a transition front progressing radially from the unit centre, while the organics are expelled towards the prism edge. Simultaneously, along the shell thickness, the growth occurs following a layer-by-layer mode. These findings open biomimetic perspectives for the design of refined crystalline materials. Statement of significance: Calcareous biominerals are amongst the most present forms of biominerals. They exhibit astonishing structural, optical and mechanical properties while being formed at ambient synthesis conditions from ubiquitous ions, motivating the deep understanding of biomineralization. Here, we unveil the first formation steps involved in the biomineralization cycle of prismatic units of two bivalve species by applying a new multi-modal non-destructive characterization approach, sensitive to chemical and crystalline properties. The observations of structural features in mineralized units of different ages allowed the derivation of a temporal sequence for prism biomineralization, involving an amorphous precursor, a radial crystallisation front and a layer-by-layer sequence. Beyond these chemical and physical findings, the herein introduced multi-modal approach is highly relevant to other biominerals and bio-inspired studies. Graphical abstract: Image, graphical abstract